ALTERATION AND MINERALIZATION STUDIES IN THE JEBLOGAN AREA, KARANGTENGAH, WONOGIRI, CENTRAL JAVA - Negara, Awang Subang (KURVATEK, 2024)
The research area is located in Jeblogan, Karangtengah, Wonogiri, Central Java. This study aims to investigate the hydrothermal alteration and mineralization. Geological structures present in the research area include faults and fractures. These faults are well-developed trending NE-SW, NW-SE, and N-S as pathways for fluid ascent to the surface, thereby influencing alteration patterns. Mineral alteration assemblages in the research area, based on petrographic, mineragraphy, and XRD analysis, result from hydrothermal processes and include mineral assemblage zones such as Quartz ± Silica ± Pyrite, Alunite + Pyrophyllite ± Zunyite ± Quartz ± Hematite, Illite + Halloysite ± Smectite ± Kaolinite ± Quartz, and Chlorite + Calcite + Epidote ± Pyrite. Mineralization found in the research area includes Chalcopyrite, Sphalerite, Pyrite, Chalcocite, and Galena. Based on the characteristic parameters of the deposit type and laboratory analysis, the deposit type at the research location is low-sulfidation epithermal deposit and intermediate-sulfidation deposit.